Reversible hydrogen storage in Mg(HxF1−x)2 solid solutions - Pighin, Santiago Alberto (2017)
Mg(HxF1−x)2 solid solutions have been synthesized by mechanical milling MgF2 and MgH2 under H2 atmosphere. Complete solubility has been observed at 475 °C. The solid solution presents a rutile-type structure with the anion site randomly occupied by H− or F− and with lattice parameters showing positive deviations from Vegard's law. The solution can be decomposed and re-formed reversibly by changing H2 pressure. For example, Mg(H0.9F0.1)2 reversibly stores 5.5 wt. % H2 in less than 3 min at 440 °C. During decomposition H2 is released, and Mg and a solution rich in F appear as products. This process takes place in two clearly marked stages controlled by F− concentration in the material. The decomposition enthalpy of the first one is close to that of MgH2 for Mg(H0.9F0.1)2, and decreases with the H content in the solution.